Hillary Clinton’s Foreign Policy Paradox - Resnick, Evan N. (2016)
Paradoxically, although US presidential candidate Hillary Clinton is relying on her extensive foreign policy experience to bolster her electoral appeal, her actual track record as a foreign policy decision maker is worrisome.